Prevalence of Depressive Symptoms in Aseptic Revision Total Knee Arthroplasty Based on the Mode of Failure - Nicole Durig Quinlan, MD, MS; Vishal Hegde, MD; Daniel N. Bracey, MD, PhD; Aviva Pollet, MS; Roseann M. Johnson, BS, CCRP; Douglas A. Dennis, MD; Jason M. Jennings, MD, DPT (Arthroplasty Today, 2024)
Background: Complications following total knee arthroplasty (TKA) that necessitate revision cause considerable psychological distress and symptoms of depression, which are linked to poorer postoperative outcomes, increased complications, and increased healthcare utilization. We aimed to identify the prevalence of mental health disorders and symptoms preoperatively and postoperatively in patients undergoing aseptic revision TKA and to stratify these patients based on their mechanism of failure. Methods: All patients undergoing aseptic revision TKA from 2008 to 2019 with a minimum 1-year follow-up were retrospectively reviewed at a single institution. Patients (n = 394) were grouped based on 7 failure modes previously described. Patients were considered to have depressive symptoms if their Veterans RAND-12 mental component score was below 42. Preoperative and postoperative Veterans RAND-12 mental component scores at the latest follow-up were evaluated. Results: Overall comparative prevalence of preoperative to postoperative depressive symptoms was 23.4%-18.8%. By mode of failure are as follows: arthrofibrosis (25.8%-16.7%), aseptic loosening (25.3%-18.9%), extensor mechanism disruption (25%-50%), failed unicompartmental knee arthroplasty (8.6%-14.3%), instability (25.7%-17.1%), osteolysis or polyethylene wear (23.1%-23.1%), and patellar failure (11.8%-23.5%). There was no difference in depressive symptoms among failure modes preoperatively (P = .376) or at the latest postoperative follow-up (P = .175). Conclusions: The prevalence of depressive symptoms in revision TKA patients appears to be independent of failure mode. Surgeon awareness and screening for depressive symptoms in this patient population preoperatively with referral for potential treatment may improve early postoperative outcomes.